Transplantation von Amnionmembran zur Rekonstruktion der Hornhautoberfläche: operatives Vorgehen - Kruse, Friedrich E.; Rohrschneider, Klaus; Völcker, Hans Eberhard (Der Ophthalmologe, 1999)
Persistent defects of the ocular surface remain a therapeutic challenge, which often requires surgical intervention. Recently, transplantation of human amniotic membrane has been suggested for reconstruction of the corneal surface. We describe two techniques using cryo-preserved amniotic membrane. Transplantation of several layers of amniotic membrane can successfully restore deep corneal ulcers associated with persistent epithelial defects. When such defects are not associated with stromal ulcers, they might benefit from amniotic membrane grafts sutured to cover the entire corneal surface. Both methods may serve as valuable tools for ocular surface reconstruction, especially in the context of impaired epithelial function.
Englische Zusammenfassung: Techniques for reconstruction of the corneal surface by transplantation of preserved human amniotic membrane
Gesehen am 03.03.2021